From Chains to Chromophores: Tailored Thermal and Linear/Nonlinear Optical Features of Asymmetric Pyrimidine-Coumarin Systems - Nicolas, Prescillia; Abdallah, Stephania; Chen, Dong; Rizzi, Giorgia; Jeannin, Olivier; Clays, Koen; Bellec, Nathalie; Bilgin-Eran, Belkis; Akdas-Kilic, Huriye; Malval, Jean-Pierre; Van Cleuvenbergen, Stijn; Camerel, Franck (MDPI, 2025)
Eleven novel asymmetric pyrimidine derivatives were synthesized. The pyrimidine core was functionalized with a coumarin chromophore and a pro-mesogenic fragment bearing either chiral or linear alkyl chains of variable length and substitution patterns. The thermal properties were investigated using polarized optical microscopy, differential scanning calorimetry, and small-angle X-ray scattering, revealing that only selected derivatives exhibited liquid crystalline phases with ordered columnar or smectic organizations. Linear and nonlinear optical properties were characterized by UV-Vis absorption, fluorescence spectroscopy, two-photon absorption, and second-harmonic generation. Optical responses were found to be highly sensitive to the substitution pattern: derivatives functionalized at the 4 and 3,4,5 positions exhibited enhanced 2PA cross-sections and pronounced SHG signals, whereas variations in alkyl chain length exerted only a minor influence. Notably, compounds forming highly ordered non-centrosymmetric mesophases produced robust SHG-active thin films. Importantly, strong SHG responses were obtained without the need for a chiral center, as the inherent asymmetry of the linear alkyl chain derivatives was sufficient to drive self-organization into non-centrosymmetric materials. These results demonstrate that asymmetric pyrimidine-based architectures combining pi-conjugation and controlled supramolecular organization are promising candidates for nonlinear optical applications such as photonic devices, multiphoton imaging, and optical data storage.
Keywords: asymmetric pyrimidine; thermal behavior; luminescence; two-photon absorption; second harmonic generation; PHOTOPHYSICS; DERIVATIVES; STORAGE; PHASE; BLOCK; Biochemistry & Molecular Biology; Chemistry